Habitat fragmentation and biodiversity conservation: key findings and future challenges - Wilson, Maxwell C.; Chen, Xiao-Yong; Corlett, Richard T.; Didham, Raphael K.; Ding, Ping; Holt, Robert D.; Holyoak, Marcel; Hu, Guang; Hughes, Alice C.; Jiang, Lin; Laurance, William F.; Liu, Jiajia; et al. (Landscape ecology, 2016)
Habitat loss and fragmentation has long been considered the primary cause for biodiversity loss and ecosystem degradation worldwide, and is a key research topic in landscape ecology.